2020
DOI: 10.21203/rs.3.rs-120518/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival Benefit of Intervention Treatment in Advanced Anaplastic Thyroid Cancer

Abstract: Background Management of anaplastic thyroid cancer (ATC) is a controversial issue; thus, proper treatment and prognostic factors should be investigated. Objectives To compare the survival outcomes of intervention and palliative treatment in ATC patients. Methods A hospital-based retrospective study was conducted in a single tertiary university hospital. The medical record charts were retrieved from November 20, 1987 to December 31, 2016. The final follow-up was ended by December 31, 2017. Patients’ demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
1
2
Order By: Relevance
“…Participants' tumour size was > 4 cm among the majority (77.3%) of participants. Previous studies reported tumours ranging between 3.6 and 10.5 cm, but only 68.9% of cases were reported to be larger than 4 cm [16,22]. Even though larger tumour sizes are bad prognostic factors [22], those with larger tumours survived longer than those with smaller ones in the current study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Participants' tumour size was > 4 cm among the majority (77.3%) of participants. Previous studies reported tumours ranging between 3.6 and 10.5 cm, but only 68.9% of cases were reported to be larger than 4 cm [16,22]. Even though larger tumour sizes are bad prognostic factors [22], those with larger tumours survived longer than those with smaller ones in the current study.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies reported tumours ranging between 3.6 and 10.5 cm, but only 68.9% of cases were reported to be larger than 4 cm [16,22]. Even though larger tumour sizes are bad prognostic factors [22], those with larger tumours survived longer than those with smaller ones in the current study. This discrepancy could be explained by the role of large size in increasing patient awareness and motivation to seek treatment at an earlier stage, thereby increasing the scope of treatment and survival prospects.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation